Collaborative Governance Dalam Pencegahan Pernikahan Usia Anak Di Kabupaten Bojonegoro - Erika, Putri Herlinia; Wulandari , Septi; Musta'ana, Musta'ana (Program Studi Administrasi Negara Universitas Serang Raya, 2023)
This research aims to find out and describe how collaboration occurs in preventing child marriage in Bojonegoro Regency. This type of research is descriptive research using a qualitative approach with four informants as research subjects. Where this subject is determined through a purposive sampling technique based on several criteria. The focus of this research is on initial conditions, institutional design, facilitative leadership and collaboration processes. Data was obtained from interviews, statutory regulations and documents related to research. The data analysis technique goes through three stages; data condensation, data presentation and conclusion drawing. Test the credibility of the data by conducting a member check. The results of the research show that collaborative governance in preventing child marriage in Bojonegoro Regency has gone quite well. Although there are several aspects that are not yet optimal in implementation, namely institutional design, facilitative leadership and face-to-face dialogue. There is an imbalance of power and resources in the initial conditions. Based on the research results, researchers recommend to the government, especially DP3AKB, to create leadership conditions that are able to empower non-government stakeholders, at least holding regular meetings once every three months to find out developments and problems related to child marriage prevention activities that have been implemented by related parties.